Extraction, Isolation, and TEMPO-NaBr-NaClO Oxidation Modification of Cellulose from Coffee Grounds - Mourad Ouhammou; Abdellah Mourak; Aziz Ait-Karra; Jaouad Abderrahim; Najat Elhadiri; Mostafa Mahrouz (Biomass, 2025)
This study investigates the extraction, isolation, and chemical modification of cellulose from coffee ground residues using TEMPO-NaBr-NaClO oxidation. These residues represent a promising renewable source of cellulose, which is obtained after the removal of impurities such as lignin (24%), hemicellulose (42%), and other compounds. The TEMPO (2,2,6,6-tetramethylpiperidine-1-oxyl radical)-catalyzed oxidation selectively converts primary hydroxyl groups into carboxylate groups (-COOH) under mild conditions in aqueous media, achieving an oxidation yield of up to 67%. Structural and morphological analyses, including scanning electron microscopy (SEM), Fourier transform infrared (FTIR) spectroscopy, and X-ray diffraction (XRD), confirm the successful chemical modification of the cellulose. The results indicate a reduction in crystallinity index from native cellulose (80%) to oxidized cellulose (65%), reflecting partial disruption of the microfibril structure and the introduction of new chemical functionalities. FTIR analysis reveals the appearance of characteristic carboxylate bands, confirming the conversion of hydroxyl groups into carboxyl groups. Energy-dispersive X-ray (EDX) analysis further highlights a significant increase in oxygen content, indicating the efficiency of the oxidation process. The TEMPO-oxidized cellulose is water-soluble, enabling the production of valuable polyelectrolytes and intermediates. These chemical modifications improve the cellulose’s reactivity, broadening its potential applications in various fields, including biocomposites, sustainable packaging materials, and functional films. This work demonstrates the feasibility of utilizing coffee ground residues as a renewable, eco-friendly source of modified cellulose for high-value applications.